AVALIAÇÃO GENÉTICA PARA A POSTURA DE CODORNAS POR MEIO DE MODELOS DE REGRESSÃO ALEATÓRIA - ROSSI, Robson Marcelo; GASPARINO, Eliane (Brazilian Journal of Biometrics, 2018)
This study aimed to present a mixed effects model Bayesian, that allows to estimate genetic parameters for daily laying of quail eggs through random regression models (RRM). As fixed effects season of birth and diet. The covariate posture of occasion was analyze model with linear, quadratic and cubic. This models present Deviance Information Criterion (DIC), respectively, 17.212, 13,.374 and 2.596, culminating in the last selection. In this model the effects of season of birth and the covariate occasion posture were significant, heterogeneous cubic tendency descending, ranging approximately 50% on average for the predicted values, over time. It was observed initially decreasing additive variance, reaching its lowest point with a variation of less than about 1% at 100 days of age and increasing from then onwards. This pattern was observed analogously to heritability whose values, on average, were approximately 23%. Genetic heterogeneity is observed over time, which indicates a larger influence of environmental factors on egg production after peak production.